2004
DOI: 10.4141/p03-123
|View full text |Cite
|
Sign up to set email alerts
|

Rate and timing of nitrogen fertilization of Russet Burbank potato: Yield and processing quality

Abstract: ) applied either at planting according to normal grower practice, or at hilling, the latest time that granular fertilizer can practically be applied. Tuber total and marketable yield, size distribution, specific gravity, fry colour and tuber concentrations of NO 3 , sucrose and glucose were measured. Increasing rates of N fertilization increased tuber yield and tuber size, increased tuber NO 3 concentration and decreased tuber specific gravity, but had little effect on tuber sugar concentrations or fry colour.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
32
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 26 publications
5
32
0
1
Order By: Relevance
“…Use of a plant bioassay approach may therefore provide more realistic estimates of soil N supply compared with vegetation-free plots because soil moisture contents more closely reflect the soil moisture contents that commercial crops would experience. Estimates of soil N supply obtained using a plant bioassay approach were previously reported to account for much of the among-year variation in the response of tuber yield to the rate of N fertilization (Zebarth et al 2004c), confirming that these estimates of soil N supply are biologically meaningful. These findings suggest that use of the plant bioassay approach is a valid way to estimate plant-available soil N supply.…”
Section: Discussionsupporting
confidence: 65%
“…Use of a plant bioassay approach may therefore provide more realistic estimates of soil N supply compared with vegetation-free plots because soil moisture contents more closely reflect the soil moisture contents that commercial crops would experience. Estimates of soil N supply obtained using a plant bioassay approach were previously reported to account for much of the among-year variation in the response of tuber yield to the rate of N fertilization (Zebarth et al 2004c), confirming that these estimates of soil N supply are biologically meaningful. These findings suggest that use of the plant bioassay approach is a valid way to estimate plant-available soil N supply.…”
Section: Discussionsupporting
confidence: 65%
“…Split N application has been shown to be effective in reducing NO 3 ( leaching losses in irrigated potato production on sandy soils (Errebhi et al 1998). However, under the rain-fed potato production in Atlantic Canada and in Maine, there is limited evidence of a benefit of split N application with respect to tuber yield or efficiency of fertilizer N utilization (Porter and Sisson 1993;Zebarth et al 2004). Rather, split N application has the potential to reduce tuber yield compared with all fertilizer N applied at planting in years with dry soil conditions (Porter and Sisson 1993;Zebarth et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, under the rain-fed potato production in Atlantic Canada and in Maine, there is limited evidence of a benefit of split N application with respect to tuber yield or efficiency of fertilizer N utilization (Porter and Sisson 1993;Zebarth et al 2004). Rather, split N application has the potential to reduce tuber yield compared with all fertilizer N applied at planting in years with dry soil conditions (Porter and Sisson 1993;Zebarth et al 2004). Therefore, while split N application has the potential to reduce N 2 O emissions, split N application is difficult to justify in terms of crop production.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports that sidedressing of N can reduce yields compared with pre-plant applications in some cases (Everaarts 1993;Sanderson and Ivany 1999). Zebarth et al (2004) concluded that for potatoes, sidedressing had questionable benefits on rain-fed crops in wet years, and can decrease yield in dry years. Observations such as these about weather and N may assist in our understanding of weather-induced variability.…”
mentioning
confidence: 99%